Correlations of phthalate metabolites in urine samples from fertile and infertile men: Free-form concentration vs. conjugated-form concentration. (August 2020) - Feng, Yong-Lai; Liao, Xiangjun; Chen, Da; Takser, Larissa; Cakmak, Sabit; Chan, Peter; Zhu, Jiping
Abstract: In previous studies, the total content of urinary phthalate metabolites was commonly used to evaluate human exposure to phthalates. However, phthalate metabolites are mainly present in urine in two forms, conjugated and free. These metabolite forms in urine are more relevant to the biotransformation pathways of the phthalates in humans. Therefore, the concentration of these forms is more relevant to exposure related health outcomes than total content. In this study, instead of measuring total content, the free- and conjugated-form concentrations of phthalate metabolites in the urine of fertile and infertile men were measured. The main metabolites in urine of both groups are monoethyl phthalate (MEP) and the di-(2-ethylhexyl) phthalate (DEHP) metabolites. The geometric means of their both conjugated- and free-forms in the infertile group were higher than in the fertile group, specifically, 24.3 and 43.4 μg/g creatinine vs 8.5 and 28.9 μg/g creatinine, respectively, for MEP, and 50.0 and 9.1 μg/g creatinine vs 39.1 and 8.4 μg/g creatinine, respectively for total DEHP metabolites. We investigated the correlations of free- and conjugated-form phthalate metabolite concentrations between the infertile and fertile group as well as among different phthalate metabolites. The results showed that there was a statistically significant difference between the infertile and fertile group for monobenzyl phthalate (MBzP) in both free-form and conjugated-form. However, there was only a statistically significant difference between the two groups for conjugated-form MEP and MEHP, and no statistically significant difference between the two groups for free-form MEP and MEHP. The results of the Pearson correlation test revealed that the correlations between DEHP metabolites and the correlations between mid-sized phthalate metabolites (mono-n-butyl phthalate (MnBP), mono-isobutyl phthalate (MiBP) and mono-benzyl phthalate (MBzP)) were stronger than between these two clusters of metabolites. This study is the first attempt to examine possible effects of conjugated-form concentrations of phthalate metabolites on human fertility. The results of this study suggest that conjugated-form and free-form concentrations of urinary phthalate metabolites may be appropriate biomarkers for assessing human exposure to phthalates and association with health outcomes. Graphical abstract: Image 1 Highlights: The correlations of phthalate metabolites in urine from fertile and infertile men were evaluated. Possible effects of conjugated-form phthalate metabolites on human fertility were examined. Both conjugated- and free-form MBzP showed a statistically significant difference between two groups. Statistically significant differences between two groups were observed for conjugated-form MEP and MEHP. Conjugated-form concentration may be a better biomarker for human exposure assessment.